HUBUNGAN DUKUNGAN SOSIAL TERDAHAP KUALITAS HIDUP PASIEN KANKER KOLOREKTAL YANG MENJALANI KEMOTERAPI ORAL DI POLI ONKOLOGI RSUD ARIFIN ACHMAD PROVINSI RIAU - Dwi Mitra Sari; Nurul Huda; Wasisto Utomo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Patients undergoing oral chemotherapy will experience a quality of lifedecrease. The quality of life can increase ifthere is a social support. This study aims to determine the relationship between social support and quality of life ofcolorectal cancer patients who undergo oral chemotherapy at RSUD Arifin Achmad in Riau Province with descriptivecorrelation research design and cross sectionalapproach. There were 43 people taken as the samples of this research.They were taken based on the inclusion criteria using purposive sampling technique. The measuring tools used werequestionnaires of social support for social support variables and questionnaire of quality of life from WHOQOL-BREFfor the quality of life variables. The analyses used were univariate analysis to know the frequency distribution andbivariate using chi-square test. The result showed that 16 respondents (69.6%) who had a negative social support, werein poor quality of life, and 7 people (30.4%) who had negative social support, were in good quality of life. Among the43 respondents who had positive social support, 6 people (30.0%) were in a poor quality of life and 14 people (70.0%)who had positive social support were in a good quality of life. Based on the result of the statistical test using chi-squaretest, which resulted in ρ value = 0,022 <α (0,05), it can be concluded that there is a correlation between social supportwith quality of life of colorectal cancer patients undergoing oral chemotherapy. Social support received by individualwere not extend the life people with serious illness, but can reduce pain and improve the quality of life of patients.Keywords: Social Support, Oral Chemotherapy, Quality of Life